Pseudomyllocerus thracicus sp. nov. from northern Greece (Coleoptera; Curculionidae; Entiminae) - Germann, Christoph; Kakiopoulos, George; Borovec, Roman (Zootaxa, 2024)
During an excursion to northern Greece, a new species of Pseudomyllocerus Desbrochers des Loges, 1872 was discovered. It is described here as Pseudomyllocerus thracicus Germann, Kakiopoulos and Borovec sp. nov. and compared to all hitherto known species of that genus. Based on the examination of specimens, the new synonymies Pseudomyllocerus canescens (Germar, 1823) = P. invreae (F. Solari, 1948) syn. nov., and P. canescens = P. ophthalmicus (Stierlin, 1888) syn. nov. are established.